2001
DOI: 10.1023/a:1010203930470
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: To study the transfer of oxidized phospholipids from cell membranes to high-density lipoproteins (HDL), human Cu2+-oxidized erythrocyte membranes were incubated with HDL3 subfraction for 17 h at 37 degrees C followed by isolation of the supernatant, precipitation from it of HDL3, and determination of lipid peroxide products (LPP) in them. The incubation increased the content of lipid hydroperoxides in HDL3 significantly (by 32 and 40% calculated per ml of sample or mg of protein) and of malondialdehyde (by 27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Calculation of the viscous flow enthalpy for the lipoprotein 32, 33 on either side of T c and the difference in these values relative to this point (Δ H trans. , the conventional heat of transition) demonstrated that with a rather high ionic force of the solution the activation energy of viscous flow was small both before T c and after it.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Calculation of the viscous flow enthalpy for the lipoprotein 32, 33 on either side of T c and the difference in these values relative to this point (Δ H trans. , the conventional heat of transition) demonstrated that with a rather high ionic force of the solution the activation energy of viscous flow was small both before T c and after it.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, an about 5 cm −1 frequency shift of the absorption band of the mentioned bond to the long wave region was observed, which was reflected on the differential curve by the appearance of asymmetry and a weak maximum at 1733 cm −1 . This can be explained by an increase in the number of hydrogen bonds that are likely to form between unesterified cholesterol and human apoA‐I in native HDL 32.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ApoA-II, along with acute-phase SAA, impairs the antioxidant properties of HDL by displacing paraoxonase-1, a HDL-associated enzyme [109,110]. Paraoxonase-1 enables HDL to accept and inactivate oxidized phospholipids from cell membranes [111]. Impairment of this function might be especially problematic in a setting of severe oxidative stress such as SCD.…”
Section: Discussionmentioning
confidence: 99%